1992
DOI: 10.1103/physrevb.45.8209
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of insulator-metal transitions in perovskites RNiO3 (R=Pr,Nd,Sm,Eu) due to closing of charge-transfer gap

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

35
721
2
8

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,000 publications
(779 citation statements)
references
References 21 publications
35
721
2
8
Order By: Relevance
“…Generally, it requires oxide reaction above 1000 o C u nder exce ss ive o xy gen p ress ure o f abo ut 2 00 bars du ri ng several days [5][6][7]. Several studies have been reported also on the dynamics of the plasma plume generated by PLD of complex oxides in a background gas [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it requires oxide reaction above 1000 o C u nder exce ss ive o xy gen p ress ure o f abo ut 2 00 bars du ri ng several days [5][6][7]. Several studies have been reported also on the dynamics of the plasma plume generated by PLD of complex oxides in a background gas [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…At low temperatures La−Ni−O system undergoes metal−to−insulator transition 7 as a function of its thickness. This happens due to electron correlation, band effect and also by spin, orbital and charge ordering.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk LNO is the only member in the ReNiO 3 series (Re: La, Pr, Nd,...etc.) that remains metallic at all temperatures 1,10 . As a result, thin film LNO and LNO-based heterostructures have been studied under various strained conditions to control the correlation strength and the metalinsulator phase transition [11][12][13][14] in an effort to find possible high temperature superconductivity 15 and conductivity enhancement 16 .…”
mentioning
confidence: 99%